Improving rice productivity, quality and soil health sustenance in Eastern Himalayas using promising rice (Oryza sativa L.) varieties and integrated nutrient management - a review - Harish M.N.; Anil K. Choudhary; Y.V. Singh; Vijay Pooniya; Varatharajan T. (Annals of Agricultural Research, 2022)
Rice (Oryza Sativa L.) is major food crop in north-eastern hilly region (NEHR) of India where 80% of arable land is occupied by rice. It is cultivated in 3.5 m ha in north-eastern states of India accounting for about 7.8% of total rice acreage of India and contributing 6.5% to national rice production. Productivity of rice in the region is very low. North-eastern (NE) region of India is already deficit in about 12% of food grains which includes about 1 million tons of rice. Major reasons for low productivity of rice are non-adoption of high yielding varieties (HYVs’), low fertilizer use and improved crop production technology besides poor socio-agro-economic situations of farmers. Reliable information on production potential of integrated nutrient management practices in promising rice cultivars is also lacking in this region. Thus, it is high time to address above issues keeping in view the significance of rice in agrarian sector of NEHR. Overall, it is summarized that integrated use of organics and chemical fertilizers is highly effective in drawing higher productivity, profitability, quality, resource use efficiency and soil health in rice and rice based production systems in NEHR.